Large volume in situ H2 production on fixed bed reactor by concentrated formic acid aqueous solution. (1st April 2018) - Tao, Yaqiu; Tao, Lulu; Pan, Zhigang; Qiu, Simin; Shen, Xiaodong
Graphical abstract: Highlights: Large volume of H2 stream up to 230 mL/min was produced with high H2 selectivity and formic acid conversion at a space velocity of 20 h −1 on a 10% Mo2 C/AC. The H2 production was in a total environmental friendly way and in a continuous mode. Catalysts used were prepared by calcination with certain precursor, which is suit for application. The 0.06% Co doped 10% Mo2 C/AC presented 100% H2 selectivity. The catalysts used remained at high H2 selectivity and the formic acid conversion stabilized at 64% during the life time study. Abstract: Formic acid is a promising hydrogen storage material for its high H2 capacity, easy transfer and moderate H2 regeneration conditions. Active carbon supported Mo2 C with or without Co doping were used as the heterogeneous catalyst in the decomposition of a high concentrated aqueous solution of formic acid up to 50% on a fixed bed reactor. For a given flow rate and reaction temperature, though higher volume of H2 is produced per unit time, the increase in formic acid's concentration reduces both H2 selectivity and formic acid conversion rate. At 250 °C, a stream of 236 mL/min H2 was generated continuously at a high H2 selectivity (91%) and formic acid conversion rate (86%), from a 10% formic acid fed at the flow rate of 5 mL/min. High reaction temperature improved the conversion of formic acid feed at little expense of H2 selectivity. The doping of Co in the Mo2 C lattice improves the H2 selectivity to 100% at 100–200 °C. A life time study showed the stability of this system by the remained high H2 selectivity in formic acid decomposition. This work of using active carbon supported molybdenum carbides and high concentrated aqueous formic acid, opens up a new route for the portable H2 generator using formic acid as a hydrogen storage material at no environmental risk.